Perencanaan Dan Perancangan Oven Pemanggang Untuk Jamu Tradisional (Empon-Empon) Sistem Rotary Tray Menggunakan Simulasi Aplikasi Komputer - YUSUF, AGUNG BUDIMAN (e-Proceeding FTI, 2024)
Drying is defined as the process of reducing the moisture content of a material until it reaches a certain moisture content so as to inhibit the rate of deterioration of the material due to biological and chemical activities. The rotary tray oven is designed based on the capacity of the oven in one work, then a stress simulation is carried out using a solidworks static simulation. This oven is used to dry traditional herbal ingredients. Abstrak Pengeringan didefinisikan sebagai proses pengurangan kadar air bahan hingga mencapai kadar air tertentu sehingga menghambat laju kerusakan bahan akibat aktifitas biologis dan kimia. Oven Rotary Tray di desain berdasarkan kapasitas oven dalam satu kali pengerjaan selanjutnya dilakukan simulasi tegangan menggunakan simulasi solidworks static simulation. Oven ini digunakan untuk mengeringkan bahan jamu tradisional.